CHRISTOLOGICAL CONCEPTIONS AND EXPRESSIONS OF THE EARLY SYRIAC AUTHORS AND WRITINGS - Kavattu, Siby Kuriakose (Asian Horizons, 2011)
The history of the Church witnesses a rich plurality in the understanding of the mystery of Christ. Different ecclesial traditions had their own Christology. East and West have different images of Christ. Lack of appreciation of the different approaches have accounted for the Christological controversies in the history of the Church. Today, however, there is a great openness from the part of the Church towards the different expressions of the Christological languages.1 This paper attempts to bring to light the less known and researched, yet valid and important Christological conceptions and expressions of the Early Syriac authors and writings for the benefit of the Christological discussions today.